2017
DOI: 10.1007/s11356-017-9773-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BPF on steroid hormone homeostasis and gene expression in the hypothalamic–pituitary–gonadal axis of zebrafish

Abstract: Bisphenol F (BPF) has been frequently detected in various environmental compartments, and previous studies found that BPF exhibits similar estrogenic and anti-androgenic effects on the mammalian endocrine system to those of bisphenol A (BPA). However, the potential disrupting effects of BPF on aquatic organisms and the underling disrupting mechanisms have not been investigated. In this study, the potential disrupting mechanisms of BPF on the hypothalamic-pituitary-gonadal (HPG) axis and liver were probed by em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…For example, expression of reproductive/neuroendocrine related genes such as kiss1 , kiss1r , gnrh3 and lhbeta was significantly increased at both 24 hpf and 120 hpf upon low level (0.045–0.45 μmol L ‐1 ) BPA or BPS exposure 46 . Additional work investigating gene expression patterns in juvenile and/or adult animals in the hypothalamic region and/or the hypothalamic‐pituitary‐gonadal axis confirmed an effect of bisphenols in adult fish 46,95,96 and juvenile rodent 97 …”
Section: Discussionmentioning
confidence: 82%
“…For example, expression of reproductive/neuroendocrine related genes such as kiss1 , kiss1r , gnrh3 and lhbeta was significantly increased at both 24 hpf and 120 hpf upon low level (0.045–0.45 μmol L ‐1 ) BPA or BPS exposure 46 . Additional work investigating gene expression patterns in juvenile and/or adult animals in the hypothalamic region and/or the hypothalamic‐pituitary‐gonadal axis confirmed an effect of bisphenols in adult fish 46,95,96 and juvenile rodent 97 …”
Section: Discussionmentioning
confidence: 82%
“…A previous study suggested that BPA might act as an estrogenic agonist in males who have low endogenous estrogen levels, and conversely act as an antagonist in females who have higher endogenous estrogen levels [36]. Sex differences in estrogenic activity were also observed for BPF in an animal study [25]. Further investigation is warranted to clarify the health effects of BPA and BPF for each sex.…”
Section: Discussionmentioning
confidence: 97%
“…BPF was also found to interfere with hormonal regulation by deregulating messenger RNA/long non-coding RNA and micro RNA in a human primary adipocyte model [24]. Moreover, BPF exhibited adverse effects on the hypothalamic-pituitary-gonadal axis, which is crucial for energy storage and consumption [2526]. Second, BPF could promote differentiation of preadipocytes and increase lipid accumulation by affecting the peroxisome proliferator-activated receptor gamma signaling pathway [1227].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the structural similarity to BPA, the analogs (BPS, BPF, BPAF) may have similar endocrine-disrupting effects to those of BPA (23, 27, 28). Studies in zebrafish have reported the disrupting effects on steroid hormones of BPS (29), BPF (30), and BPAF (31). However, the potential harmful effects on glucose homeostasis of these BPA substitutes, which were used more and more widely and frequently in our daily life, are still unknown.…”
Section: Introductionmentioning
confidence: 99%